Higher Education in Developing Countries: Peril and Promise, a Decade and a Half Later: Development Lost? - Halvorsen, Tor (International Journal of African Higher Education, 2016)
The author of this article argues that the Task Force behind the Peril and Promise report created a document that represents a silent compromise between what he calls “UNESCO values” and what is seen as “World Bank values.” In the years after the report was written, development has been mostly shaped by WB values. The question is raised whether this is partly due to a weakening of UNESCO as an oppositional force to the hegemonic trend of neoliberalism and academic capitalism. In conclusion, the article advocates that we need to opt again for a development of universities based on UNESCO values. We have to engage in an analytical evaluation of the present hegemony of academic capitalism, and argue more strongly for the alternative: higher education and research as part of culture and the public space, and as a precondition for strengthening democracy through academic freedom. — L’auteur de l’article soutient que le Groupe de Travail responsable du rapport « Périls et Promesses » a réalisé un document qui représente un compromis tacite entre ce qu’il appelle “les valeurs de l’UNESCO” et ce que l’on considère comme “les valeurs de la Banque mondiale”. Dans les années qui ont suivi la publication du rapport, le développement a été principalement influencé par les valeurs de la Banque mondiale. La question posée ici est de savoir si ceci serait dû en partie à un affaiblissement de l’UNESCO en tant que force d’opposition à l’hégémonie croissante du néolibéralisme et du capitalisme académique. En conclusion, l’article préconise de remettre les valeurs de l’UNESCO à la base du développement des universités. Il faut entreprendre un examen analytique de l’hégémonie actuelle du capitalisme académique, et soutenir plus vigoureusement le modèle alternatif : l’enseignement supérieur et la recherche comme parties intégrantes de la culture et de l’espace public, et comme condition préalable au renforcement de la démocratie par le biais de la liberté académique.